PETROLOGY AND MINERAL CHEMISTRY OF THE ALKALINE DISTRICT OF LAGES, SC, BRAZIL - Traversa, G.; Schelbe, L. F.; Barbieri, M.; Beccaluva, L.; Coltorti, M.; Conte, A. M.; Garbarino, C.; Gomes, C. B.; Macciotta, G.; Morbidelli, L.; Ronca, S. (Geochimica Brasiliensis, 2011)